2017
DOI: 10.1186/s12868-017-0346-3
|View full text |Cite
|
Sign up to set email alerts
|

Upregulation of the endothelin A (ETA) receptor and its association with neurodegeneration in a rodent model of glaucoma

Abstract: BackgroundPrimary open angle glaucoma is a heterogeneous group of optic neuropathies that results in optic nerve degeneration and a loss of retinal ganglion cells (RGCs) ultimately causing blindness if allowed to progress. Elevation of intraocular pressure (IOP) is the most attributable risk factor for developing glaucoma and lowering of IOP is currently the only available therapy. However, despite lowering IOP, neurodegenerative effects persist in some patients. Hence, it would be beneficial to develop approa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
22
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 29 publications
(33 reference statements)
3
22
0
1
Order By: Relevance
“…The results showed that each year added to the age increases the possibility for early glaucoma changes to appear 1.243 times. It is well established that glaucoma is an age-related disease [18], which was supported by our results. Every 1 pg/mL increase in the ET-1 plasma concentration increased the possibility for early glaucoma changes to appear by 2.124 times.…”
Section: Resultssupporting
confidence: 92%
See 3 more Smart Citations
“…The results showed that each year added to the age increases the possibility for early glaucoma changes to appear 1.243 times. It is well established that glaucoma is an age-related disease [18], which was supported by our results. Every 1 pg/mL increase in the ET-1 plasma concentration increased the possibility for early glaucoma changes to appear by 2.124 times.…”
Section: Resultssupporting
confidence: 92%
“…The progression of the disease is related to some degree of restoration of ETR-A, whereas ET-1 is permanently high. These observations are related to some theories about the glaucoma pathogenesis [18], but require further investigation.…”
Section: Resultsmentioning
confidence: 52%
See 2 more Smart Citations
“…Glaukompatienten, die eine Schadensprogression aufweisen, haben im Vergleich zu den Glaukompatienten mit stagnierendem Schaden einen erhöhten Plasmaendothelinspiegel [39]. Im Weiteren ist die Rolle des Endothelins beim Glaukom nicht nur auf die Regulation der Perfusion beschränkt; kürzlich publizierte Studien zeigen, dass eine Überexpression der ET-Rezeptoren nach der Stimulation durch den erhöhten Augendruck sowohl im anterioren als auch im posterioren Augensegment bei Ratten stattfindet [40]. Somit kann Endothelin sowohl bei der Regulation des Augendruckes als auch bei der Steuerung der Neurodegeneration beteiligt sein.…”
Section: Endothelin Im Augeunclassified